Combination of a Synthetic Bioceramic Associated with a Polydioxanone-Based Membrane as an Alternative to Autogenous Bone Grafting - Frigério, Paula Buzo [UNESP]; de Moura, Juliana [UNESP]; Pitol-Palin, Letícia [UNESP]; Monteiro, Naara Gabriela [UNESP]; Mourão, Carlos Fernando; Shibli, Jamil Awad; Okamoto, Roberta [UNESP] (MDPI, 2024)
The purpose of this study was to evaluate the repair process in rat calvaria filled with synthetic biphasic bioceramics (Plenum® Osshp-70:30, HA:βTCP) or autogenous bone, covered with a polydioxanone membrane (PDO). A total of 48 rats were divided into two groups (n = 24): particulate autogenous bone + Plenum® Guide (AUTOPT+PG) or Plenum® Osshp + Plenum® Guide (PO+PG). A defect was created in the calvaria, filled with the grafts, and covered with a PDO membrane, and euthanasia took place at 7, 30, and 60 days. Micro-CT showed no statistical difference between the groups, but there was an increase in bone volume (56.26%), the number of trabeculae (2.76 mm), and intersection surface (26.76 mm2) and a decrease in total porosity (43.79%) in the PO+PG group, as well as higher values for the daily mineral apposition rate (7.16 µm/day). Histometric analysis presented material replacement and increased bone formation at 30 days compared to 7 days in both groups. Immunostaining showed a similar pattern between the groups, with an increase in proteins related to bone remodeling and formation. In conclusion, Plenum® Osshp + Plenum® Guide showed similar and sometimes superior results when compared to autogenous bone, making it a competent option as a bone substitute.
Keywords: bioceramics; bone grafting; bone substitutes; guided bone regeneration; guided tissue regeneration; synthetic polymer